Preliminary Study of Polyacrylonitrile (PAN)/Manganese Oxide Activated Carbon Nanofibers for Cd (II) Adsorption - Abdullah, N.; Yusof, N.; Jaafar, J.; Ismail, A. F.; Che Othman, F E; Salleh, W. N. W.; Misdan, N. (Journal of Applied Membrane Science & Technology, 2017)
In this work, activated carbon nanofibers (ACNFs) from precursor polyacrylnitrile (PAN) and manganese oxide (MnO2) were prepared via electrospinning process. The electrospun PAN/MnO2-based ACNFs were characterized in term of its morphological structure, functional group analysis and specific surface area using SEM-EDX, FTIR and BET analysis respectively. The comparative adsorption study of cadmium (II) ions from aqueous solution between the neat ACNFs, composite ACNFs and commercial granular activated carbon was also conducted. SEM analysis illustrated that composite ACNFs have more compact fibers with presence of MnO2 beads with smaller fiber diameter of 437.2 nm as compared to the neat ACNFs which is 575.5 nm. BET analysis elucidated specific surface area of ACNFs/MnO2 to be 67 m2/g. Under adsorption study, it was found out that Cd (II) removal by ACNFs/MnO2 was the highest (97%) followed by neat ACNFs (96%) and GAC (74%).